Analysis of the Causes of Domestic Violence among Women in Lubuk Basung District, Agam Regency - Delima; Resty Noflidaputri; R. Firwandri Marza; Deharnita (Miracle Journal Get Press, 2024)
(WHO), thirty percent of women worldwide have been victims of either non-partner sexual violence, relationship sexual violence, or both types of abuse. In West Sumatra Province, there were 964 violent cases, 311 of which involved male victims and 754 included female victims. There were 754 female victims of violence, or 27.92 percent of all women, per 100,000. 791 children were victims of violence, representing 4.34 percent of all victims (Kemenpppa, 2023). The aim of the research was to examine the reasons behind domestic abuse of women in Lubuk Basung District, Agam Regency. This qualitative study used an informant phenomenology design. The 11 informants came from the Agam District DALDUKKBPPPA Office, Toma di Naga Sub-district, and female victims. The study was conducted from August 23 to September 20, 2023. Data were collected through observation, interviews, and document review. After that, the data was analyzed, presented, and conclusions were drawn.The results of the current policy input research are limited to the relevant agencies and the amount of funds and human resources available for the program. Existing facilities and infrastructure must be supported by the APBD. Many factors can lead to domestic violence, including third persons, jealousy, financial problems, and drug use.Due to lack of funding and resources, the program did not meet expectations.The conclusion is that programs and information media should be improved to maximize prevention services and decrease domestic violence cases.